Strengthening Indonesian Language Literacy through PHBS Education at Kabanjahe Advent Private Senior High School - Ernawati Br Barus; Vera Charoline Br Barus; Etti Destinasari Telaumbanua (Global Sustainability Research Institute, 2026)
Low reading interest and literacy skills among senior high school students are often accompanied by limited awareness of Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS) in the school environment. This community service activity aimed to strengthen Indonesian language literacy among students of SMA Swasta Advent Kabanjahe through a PHBS education approach integrated with reading activities and inspirational story-writing training. The program combined lectures, interactive discussions, structured literacy activities, and creative writing workshops involving tenth-grade students. A one-group pre-test–post-test design was employed to evaluate changes in students' PHBS knowledge, complemented by content analysis of their written works. The findings demonstrated a substantial improvement in students' understanding of PHBS following the intervention, accompanied by a marked reduction in the proportion of students with low levels of knowledge. In addition, the program resulted in a collection of inspirational stories reflecting students' understanding and internalization of PHBS values. These findings suggest that integrating literacy development with health education provides an effective and engaging learning strategy that can be replicated in other schools while supporting the implementation of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) and school-based health promotion programs.